PREDIKSI STUNTING PADA BALITA DI RUMAH SAKIT KOTA SEMARANG MENGGUNAKAN NAIVE BAYES - Widya Cholid Wahyudin; Fida Maisa Hana; Agung Prihandono (JURNAL ILMU KOMPUTER DAN MATEMATIKA, 2023)
Stunting is chronic malnutrition caused by insufficient nutritional intake over a long period of time due to the provision of food that is not in accordance with needs. This study focuses on malnutrition in toddlers. Stunting in toddlers is more common in toddlers aged 12-59 months than toddlers aged 0-24 months. Stunting can have short and long-term impacts. This study used toddler data for 2018 which was obtained from the Semarang City Health Center with toddlers aged 0-59 months. This research aims to value the classification results of stunting nutritional status in toddlers using the Naive Bayes Classifier algorithm. The Naive Bayes Classifier algorithm is one of the algorithms used for the classification process that can solve problems with large amounts of data so that it can produce a probability value for a hypothesis that is sought. It is proved by the results of testing with the Naive Bayes Classifier algorithm, which was carried out on all data in a dataset of 300 records, the accuracy achieved is 85.33%.